Corrosion behavior of pure titanium in artificial saliva solution - Mariano,N.A. (2009)
The biocompatibility of commercially pure (cp) titanium stems from its chemical stability within an organism, due to a fine film of impermeable titanium oxide covering the metal surface, which guarantees its resistance to corrosion. Despite its biocompatible characteristic, this material does not promote the formation of a hydroxyapatite layer, therefore, many research groups have sought to alter the material's surface, introducing modifications that might influence corrosion resistance. The electrochemical behavior of cp Ti, with hydroxyapatite coating and without hydroxyapatite coating, commonly used in implant materials, was investigated using an artificial saliva solution at 25ºC and pH=7.4. In the conditions of the study it was observed that the hydroxyapatite layer influences the properties of corrosion resistance. This study of the behavior of cp Ti with and without hydroxyapatite coating, in naturally aerated artificial saliva solution at 25ºC, was based on open circuit potential measurements and potentiodynamic polarization curves. At approximately 1x10-6 A/cm² the potential for cp Ti with and without hydroxyapatite coating begins to increase at a faster rate, but at -74mV (SCE) for coated cp Ti and at 180mV (SCE) for uncoated cp Ti the increase in potential begins to slow. This behavior, characterized by a partial stabilization of current density, indicates that in those potential ranges a protective passive film is formed.